Development and Mechanical Performance of a New Kind of Bridge Seismic Isolator for Low Seismic Regions - H. Zhang; J. Li; T. Peng (Shock and Vibration)
The concept of fibre-reinforced plate elastomeric isolator (FRPEI) is introduced firstly in this paper. Three FRPEI specimens have been constructed to evaluate the mechanical performance of the isolators by performing vertical and horizontal tests. The research focuses on the compression stiffness, the shear stiffness, the hysteretic characteristic and the vertical bearing capacity of the isolators. The experimental results show that the mechanical performance of FRPEIs can meet the requirements of bridge rubber bearings and the energy dissipation capacity is better than that of general laminated rubber bearings. Therefore, it is feasible to use FRPEIs in seismic isolation of short span bridges in low seismic regions. Theoretical and finite element methods have also been employed and the deformation assumptions applied in the theoretical method are also verified by FEM. By comparing the differences of the results of different methods, the effectivenesses of the theoretical and finite element methods are evaluated and some considerations on isolator design are proposed.